2008
DOI: 10.1099/vir.0.83357-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional entry of dengue virus into Aedes albopictus mosquito cells is dependent on clathrin-mediated endocytosis

Abstract: Entry of dengue virus 2 (DENV-2) into Aedes albopictus mosquito C6/36 cells was analysed using biochemical and molecular inhibitors, together with confocal and electron microscopy observations. Treatment with monodansylcadaverine, chlorpromazine, sucrose and ammonium chloride inhibited DENV-2 virus yield and protein expression, whereas nystatin, a blocker of caveolae-mediated endocytosis, did not have any effect. Using confocal microscopy, co-localization of DENV-2 E glycoprotein and the marker protein transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
159
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(174 citation statements)
references
References 61 publications
12
159
0
3
Order By: Relevance
“…MDC is a pharmacological inhibitor of receptor-mediated endocytosis [18,21], while filipin, which binds cholesterol in the plasma membrane, impairs the invagination and subsequent internalisation of caveolae [23,24]. Under our experimental conditions, pretreatment of HAEC with MDC (43 mmol/l) for 30 min completely blocked the uptake of Alexa Fluor 488-labelled C-peptide (p<0.01 vs control) (Fig.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…MDC is a pharmacological inhibitor of receptor-mediated endocytosis [18,21], while filipin, which binds cholesterol in the plasma membrane, impairs the invagination and subsequent internalisation of caveolae [23,24]. Under our experimental conditions, pretreatment of HAEC with MDC (43 mmol/l) for 30 min completely blocked the uptake of Alexa Fluor 488-labelled C-peptide (p<0.01 vs control) (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…Isolation of endosomes and analysis of C-peptide content To identify early endosomes, we followed the internalisation of Alexa Fluor 488-conjugated human transferrin, a ligand known to enter the cells by clathrin-mediated endocytosis and a specific marker of early endosomes [21], in the presence of Alexa Fluor 546-labelled C-peptide in UASMC in the incubator for 10 min. Endosomes were isolated from other subcellular compartments by centrifugation (modified from [22]) and an aliquot of both the pellet and the endosome-containing supernatant fraction was used to quantitate Alexa Fluor 488-transferrin and Alexa Fluor 546-C-peptide fluorescence spectra by using a scanning spectrofluorometer.…”
Section: Methodsmentioning
confidence: 99%
“…During a blood meal of a dengue-infected person by Aedes mosquito, dengue virus (DENV) is ingested into the mosquito's midgut. It is generally believed that the mosquito midgut carries important cellular membrane receptors that facilitate viral entry through receptor-mediated endocytosis [2,3], enabling replication and exocytosis, followed by DENV disseminations to salivary glands for transmission to humans [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In past decades, the entry of JEV into host cells, either mammalian or mosquito, was demonstrated to be significantly influenced by treatment with bafilomycin A1 (Andoh et al, 1998;Nawa, 1998). In fact, a number of flaviviruses like West Nile virus (Jiang et al, 2005), DENV (Acosta et al, 2008) and JEV (Chai et al, 2013), have been known to infect host cells via this pathway. Furthermore, the cationic amphiphilic drug chlorpromazine can interfere with the entry process (Chai et al, 2013;Nawa et al, 2003), revealing that the mode of infection is receptormediated endocytosis and is clathrin-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Orthobunyavirus, one of the encephalitic arboviruses, reportedly infects mammalian host cells via clathrin-mediated endocytosis as its primary mechanism (Hollidge et al, 2012). This mechanism for infecting host cells is also implemented by various mosquito-borne flaviviruses (Acosta et al, 2008;Chu & Ng, 2004). Among them the Japanese encephalitis virus (JEV), which infects host (either mammalian or mosquito) cells via receptor-mediated endocytosis (Andoh et al, 1998;Nawa, 1998), has also been confirmed to be clathrindependent (Chai et al, 2013;Yang et al, 2013), except for certain unusual cases (Kalia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%